FACTORS INFLUENCING THE INTEGRITY OF FINANCIAL STATEMENTS - Irianto, Bambang; Suyono, Eko; Imeri, Amir (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2025)
The conflicting findings on factors affecting the integrity of financial reports from previous studies served as the main problem of this study. Therefore, it aims at examining the impact of corporate governance mechanisms (i.e., institutional ownership, managerial ownership, independent commissioners, and audit committee), auditor industry specialist, and firm size on the integrity of financial statements, with COVID-19 as a control variable. Using purposive sampling and selecting a total of 74 manufacturing companies (i.e., 518 observations over seven years from 2018 to 2024), the findings showed that institutional ownership, managerial ownership, independent commissioners, and COVID-19 did not influence the integrity of financial statements. On the other hand, the auditor industry specialist, the audit committee, and firm size had a favorable impact on the integrity of financial statements. The practical implication of these findings was that company management should prioritize the use of industry-specialized auditors and enhance the role of the audit committee in overseeing financial reporting.